(untitled) (Historia, 2021)
English This article presents a case-study in forced removals and its ramifications from 1905 to 1977 from the perspective of socio-environmental history. The focus area is a township in Pretoria called Lady Selborne (currently known as Suiderberg) and Ga-Rankuwa, where some of the displaced were relocated. The article demonstrates that forced removals did not only result in people losing their historical land, properties and material possessions, but that they also lost their “home” and thus their sense of being and of connectedness. Hence the focus is on the changing perceptions of people in the midst of their land loss, which is the focus that is lacking in academia. The article depicts the complex picture of the ramifications of forced removals among the former inhabitants of Lady Selborne. The latter was a “home” – a place for being human, where the residents managed to engage in food production and were able to own properties in an area that was multiracial. In the case of Lady Selborne, Africans were displaced from a scenic area that was fertile, close to the city centre of Pretoria and relocated to Ga-Rankuwa, a place with infertile soil on the outskirts of Pretoria. The article illustrates that successive white governments and many scholars have tried to downplay African environmental ethics and to disregard them as “superstition”. This resulted in forced removals and consequently in Africans ending up being apathetic to environmental issues in the resettlement area of Ga-Rankuwa. Environmental apathy emerged unconsciously as a weapon of opposition against removals. Afrikaans “ŉ Tuiste maak jou Motho” – die rol van die konsepte “Menswees”, “Tuiste” en Geskiedenis in Lady Selborne se gedwonge verwyderings, van ongeveer 1905 tot 1977 Hierdie artikel is ŉ gevalle-studie uit die oogpunt van sosioomgewingsgeskiedenis oor gedwonge verwyderings en die nagevolge daarvan tussen 1905 en 1977. Die fokusgebied is ŉ township in Pretoria, Lady Selborne (tans bekend as Suiderberg), en Ga-Rankuwa, waar sommige van die verplaasde mense hervestig is. Die betrokke mense het nie net hulle historiese blyplekke, eiendomme en besittings verloor nie, maar ook hulle “tuiste”, insluitend hulle selfbewussyn en hulle samehorigheidsgevoel. Die soeklig word dus op die wisselende persepsies van mense te midde van hulle eiendomsverlies gefokus – ŉ benadering wat tot dusver afwesig in akademia was. In hierdie artikel word die komplekse gevolge wat die gedwonge verskuiwings vir die voormalige inwoners van Lady Selborne gehad het, bepaal. Lady Selborne was ŉ “tuiste”, ŉ heenkome vir mense, waar die inwoners voedsel suksesvol geproduseer het en eiendomme in ŉ veelrassige gebied kon besit. Swartes is verplaas vanuit ŉ vrugbare gebied, geleë naby die stadskern van Pretoria met ŉ mooi uitsig, en is hervestig in Ga-Rankuwa, ŉ onvrugbare plek aan die buitewyke van die area. Daar word aangetoon dat opeenvolgende blanke regerings, asook talle navorsers probeer het om die omgewingsetiek van Afrika as onbelangrik en selfs as bygeloof af te maak. Gedwonge verskuiwings het gevolg en swartes het uiteindelik in Ga-Rankuwa apaties teenoor omgewingskwessies begin staan, asof hulle daardeur, in die onderbewussyn, apatie as wapen teen gedwonge hervestiging kon gebruik.